An Experience of “Subfascial Endoscopic Perforator Surgery” in Chronic Venous Insufficiency at Sir Ganga Ram Hospital, Lahore (Journal of Fatima Jinnah Medical University, 2018)
Background: In varicose veins disease the incompetent perforators has a major contribution in the development of complications. Conventionally, in patients that have associated incompetent perforators require multiple incisions for ligation of these perforators. The advancement in the endoscopic techniques has permitted the use of this modality for perforator surgery.Objective: To study the outcome and post-operative complication of Subfascial Endoscopic Perforator Surgery (SEPS) for treating complicated chronic venous insufficiency.Methods: A total of twenty patients were included in this non randomized interventional study.conducted at surgical department of Sir Ganga Ram Hospital Lahore. The data was collected from September 2011 till March 2013. Non probability purposive sampling technique was used for sample selection.Results: A total of 21 procedures were performed in 20 patients having mean age of 41.1 years. An average of four perforators were dealt with endoscopic surgery. Post-operative pain, hematoma 14.2%, edema in 5 cases (28.7%), surgical emphysema at port site in 5 patients (28.7%), bleeding due to slippage of clip in one patient (4.76%), saphenous neuralgia in one patient (4.76%) were main complications.Wound infection not seen in any case and there was no evidence of wound infection recorded during one month post-operatively. Mean hospital stay was 1.5days. At 1 month follow up ulcers healing was 90% in patients with active ulcers.Conclusion: SEPS is a better and minimally invasive technique as compared to old Linton approach for management of venous ulcers leading to early patient mobility, early return to work and better ulcer healing.
Keywords: Subfascial Endoscopic Perforator Surgery (SEPS), Venous Ulcers, chronic venous insufficiency.